A re-engineered immunotoxin shows promising preclinical activity in ovarian cancer. Issue 1 (December 2017) - Kollmorgen, Gwendlyn; Palme, Klara; Seidl, Annette; Scheiblich, Stefan; Birzele, Fabian; Wilson, Sabine; Clemens, Christian; Voss, Edgar; Kaufmann, Martin; Hirzel, Klaus; Rieder, Natascha; Krippendorff, Ben-Fillippo; et al.
Abstract RG7787 is a re-engineered mesothelin-targeted immunotoxin with reduced immunogenicity composed of a humanized anti-mesothelin Fab fragment and a B-cell epitope silenced 24 kD fragment ofPseudomonas exotoxin A. High prevalence of mesothelin-positive cases and a large unmet medical need make ovarian cancer a promising indication for the clinical development of RG7787. However, ovarian cancer patients also frequently have elevated serum levels of the cancer antigen 125 (CA-125). In principle this could pose a problem, since the binding sites for CA-125 and RG7787 on mesothelin were reported to overlap. However, we show here that RG7787 can readily displace even excess amounts of CA-125 in different cellular assays. Moreover when testedin-vitro on a panel of 12 ovarian cancer cell lines, RG7787 had high cytotoxic activity on COV644, Caov-4, and SNU-119 cells and fully inhibited growth of EFO-21, KURAMOCHI, OVSAHO, and Caov-3 cells with potency values ranging from 1 to 86 pM. Finally, we evaluated thein-vivo efficacy of RG7787 in OvCa6668, a patient-derived ovarian cancer model with high levels of CA-125 expression. RG7787 had moderate monotherapy efficacy but in combination with standard chemotherapies (cisplatin, paclitaxel) achieved pronounced tumor regressions. In summary our data support clinical testing of RG7787 in ovarian cancer.